Anxiety, anticipation and contextual information: A test of attentional control theory. Issue 6 (17th August 2016) - Cocks, Adam J.; Jackson, Robin C.; Bishop, Daniel T.; Williams, A. Mark
Abstract : We tested the assumptions of Attentional Control Theory (ACT) by examining the impact of anxiety on anticipation using a dynamic, time-constrained task. Moreover, we examined the involvement of high- and low-level cognitive processes in anticipation and how their importance may interact with anxiety. Skilled and less-skilled tennis players anticipated the shots of opponents under low- and high-anxiety conditions. Participants viewed three types of video stimuli, each depicting different levels of contextual information. Performance effectiveness (response accuracy) and processing efficiency (response accuracy divided by corresponding mental effort) were measured. Skilled players recorded higher levels of response accuracy and processing efficiency compared to less-skilled counterparts. Processing efficiency significantly decreased under high- compared to low-anxiety conditions. No difference in response accuracy was observed. When reviewing directional errors, anxiety was most detrimental to performance in the condition conveying only contextual information, suggesting that anxiety may have a greater impact on high-level (top-down) cognitive processes, potentially due to a shift in attentional control. Our findings provide partial support for ACT; anxiety elicited greater decrements in processing efficiency than performance effectiveness, possibly due to predominance of the stimulus-driven attentional system.